The experiences of young people with chronic illness in New Zealand: A qualitative study. (15th July 2019) - Sligo, Judith; Jones, Bernadette; Davies, Cheryl; Egan, Richard; Ingham, Tristram; Hancox, Robert J.; Richards, Rosalina
Abstract: Background: Around 10% of young people suffer from chronic health conditions, and their health care needs are different from those of children or adults. Most research about young people's chronic illness focuses on specific conditions, on younger children's experience, and on the perspectives of parents. This study explored the experiences of young people with two very different chronic conditions (asthma and cancer) and their perception of the New Zealand health system's response to their needs. Methods: This was a collaborative research process where eight young co‐researchers who had asthma or cancer were employed to work alongside the research team to develop protocols, interview peers, and assist with analysis. The challenges of this process are described in the article. Twenty‐one young people between ages 15 and 27 from two urban areas of New Zealand participated in semistructured open‐ended interviews about their health care experiences. Sixteen participants were female, and five male. Eleven of the participants had finished cancer treatment (with an average of 3.6 years since diagnosis), and 10 had asthma. Purposeful sampling meant that 80% of the participants with asthma were identified as Māori and the other participants identified with a range of other ethnic groups. Data were thematically coded, and coresearchers were consulted to derive the ultimate findings. Results: Chronic illness disrupted the trajectory of young people's lives and had significant effects on their relationships. The New Zealand health system generally did not respond well to the needs of these young people, but many encountered extraordinary individuals who supported them effectively. The experiences of some indigenous participants indicate that health professionals require effective cultural competence training. Conclusions: This study provides insights into how young people with very different conditions experience the health system. Young people should be consulted and actively included in decision making about making health systems responsive to their diverse needs.